Reconsidering Multilingual Education An Answer to Whys and Hows - Pallavi (JOURNAL OF INDIAN EDUCATION, 2017)
The importance of mother tongue education, of recognising pluralities and of integrating the school knowledge into social, economic and ethnic backgrounds of children has been posited in the foreword of India’s National Curriculum Framework (NCF–2005) and reiterated throughout the document. Numerous lines in the curriculum framework have been devoted to emphasise on the significance of utilising multilingualism as a resource in the classrooms. What remains unclear though, is how teachers are to translate this vision of multilingual education provided in the curriculum framework into reality. There are several practical questions that have remained unanswered. Further, the literature existing in the field shows that teachers (especially those who are ‘inservice’) are often unaware of the theoretical underpinnings that support the vision that is idealised by experts who craft national documents such as the curriculum framework. Disregarding such issues, NCF–2005 seldom explicates the theories that support the model of multilingual education that it has proposed. Unwarranted by theoretical framework or research, the statements that have been given in the curriculum framework remain suspended in the air, unable to bring the required perspectival shift in teachers (Batra, 2005). It is crucial to understand that if teachers are to translate the vision of national curriculum framework into their day-to-day classroom practices, not only must they be apprised with the theories and research that argue in the favour of multilingual education, but they must also be acquainted with the methodologies that collocate with these theories.